Problem Penggunaan AI (Artificial Intelligence) dalam Bidang Pendidikan - Budiyono, Slamet; Azhari, Pebri; Pamungkas, Maulana Al Bana (Al-DYAS, 2024)
Artificial intelligence (AI) has become an increasingly important research subject in various fields, including education. In the educational context, the use of AI promises a fundamental transformation in the way we teach and learn. However, despite AI's enormous potential to improve the efficiency and effectiveness of education, there are a number of challenges that need to be overcome. The purpose of this research is to provide readers with the view that apart from the many positive sides of AI, there are also negative sides. This research focuses on the negative side of using AI in the education sector. The method used is library research. However, if managed wisely, the use of AI in education can provide significant benefits. For example, AI can be used to personalize learning, enabling teaching tailored to each student's individual needs. Additionally, AI can help in automated grading, freeing up teachers' time to focus on direct interactions with students. By considering existing challenges and exploiting the opportunities offered by AI, education can make significant progress in improving its quality and accessibility. Therefore, further research and development is needed to overcome technical and ethical obstacles to the application of AI in education, while ensuring that its benefits are widespread and non-discriminatory.